Path Analysis on the Determinants of Depression Symptom in Elderly: A PRECEDE PROCEED Model - Zela Tunurrohmin; RB. Soemanto; Eti Poncorini Pamungkasari (Masters Program in Public Health, 2019)
Background: Mental health problems such as depression get less attention. This is due to the stigma that depression and mental health are things that do not need special attention. The population with the highest level of depression in Indonesia is experienced by the elderly. Depression in the elderly is caused by health factors, loss of loved ones and peer support and family support. The purpose of this study was to analyze the determinants of depressive symptoms in elderly.Subjects and Method: This was a cross sectional study conducted in Surakarta, Central Java, from September to October 2019. A sample of 200 elderly aged >60 years old was selected by cluster random sampling. The dependent variable was depressive symptoms. The independent variables were gender, education, employment status, marital status, residence, morbidity, family support, and peer support. The data were collected by questionnaire and analyzed by path analysis.Results: The risk of depressive symptoms in the elderly increased with the elderly who did not have a partner (b= 8.42; 95% CI= 5.75 to 11.1; p <0.001), female gender (b= 4.83; 95% CI = 2.38 to 7.27; p<0.001), elderly who do not work (b= 2.85; 95% CI= 0.32 to 5.38; p= 0.027), have morbidity (b= 12.53; 95% CI= 0.16 to 4.89; p= 0.036). The risk of depressive symptoms in the elderly decreased with strong peer support (b= -2.79; 95% CI= -5.01 to -0.56; p= 0.014), strong family support (b = -8.67; 95% CI = -11.38 to - 5.97; p <0.001). The risk of depressive symptoms was indirectly affected by education and residenceConclusion: The risk of depressive symptoms in the elderly increases with the elderly who do not have partners, gender, employment status, and morbidity. The risk of depressive symptoms in the elderly decreases with peer support, family support. The risk of depressive symptoms is indirectly affected by education and residence.Keywords: depression symptoms, elderlyCorrespondence: